Methodology for assessing herd immunity to the SARS-CoV-2 virus in the context of the COVID-19 pandemic - A. Yu. Popova (Sankt-Peterburg : NIIÈM imeni Pastera, 2021)
Serological monitoring of the study of population immunity to the SARS-CoV-2 virus in the context of COVID-19 pandemic is a necessary component in epidemiological surveillance, since population epidemiological wellbeing in a context of COVID-19 is determined by state of population immunity to the SARS-CoV-2 virus. The population herd immunity is the limiting factor in spread of the SARS-CoV-2 virus. Information on the state of population immunity is necessary to make a forecast for development of epidemiological situation, as well as to plan measures for specific and non-specific prevention of COVID-19. In this regard, the study of population immunity during the pandemic is necessary to predict development of the epidemic and identify features of epidemic process in any certain region and in the country in general. In May 2020, the Rospotrebnadzor program “Assessment of population immunity to the SARS-CoV-2 virus in the population of the Russian Federation in the context of the COVID-19 pandemic” was developed taking into account WHO recommendations in the format of a longitudinal cohort study with age stratification: at the first stage, a cohort of volunteers is formed; at the second and subsequent stages, the cohort of volunteers formed at the first stage is subject to examination; the number of stages depends on the epidemiological situation. In addition to age-related randomization while forming a cohort, at the first stage, the principle of population coverage uniformity was observed, the participation of volunteers from one institution was excluded, and the use of donated blood or patient blood from medical organizations was excluded. The survey was carried out among 7 age groups of healthy children and adults, regardless present or absent previous COVID-19 disease. Due to the fact that the population study is carried out in the context of COVID-19 pandemic, the optimal timing for collecting biomaterial at each stage is no more than 5–7 days. Questioning, selection of volunteers, their registration for blood donation, as well as processing of the results at the first stage, as well as the implementation of the second and subsequent stages of the Program are carried out only by using cloud service technology. This Program and the technology for its implementation have been successfully tested in 26 regions of the Russian Federation during the implementation of four stages from June 2020 to March 2021. Thus, at present, Rospotrebnadzor has developed a methodology and created an effectively working system of serological monitoring to assess level of herd immunity in different regions of the Russian Federation to predict the epidemiological situation, develop recommendations, and plan vaccination.